Penerapan Pola Hidup Bersih Dan Sehat Untuk Mencegah Penyakit Infeksi (Demam Tifoid) Di Kelurahan Tanah Loe Kecamatan Gattarangkeke Kabupaten Bantaeng - Tuty Widyanti; Darmawaty Rauf (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2020)
Abstract Typhoid fever is an acute febrile illness caused by infection with Salmonella typhi with an incubation period of 1-2 weeks and causes clinical symptoms such as high fever, anorexia, malaise, muscle aches, headaches, coughing, constipation to cause intestinal bleeding perforation. Transmission of these germs can be through food and drinks (Food), fingers or nails (Fingers), flies (Fly), feces (Stool), and vomiting (Fomitus). The lack of knowledge about applying clean and healthy lifestyles in the community in both urban and rural areas is one of the factors in the high incidence of typhoid fever. Communities in Tanah Loe Village, Garrangkeke Subdistrict, Bantaeng Regency, South Sulawesi, who are predominantly farmers' livelihoods have the possibility of being infected with typhoid fever with the risk of work related to hygiene.. Therefore, this counseling team provides a solution in the form of efforts to increase knowledge about clean and healthy lifestyles to avoid risk factors increasing the number of people affected by typhoid fever, especially in Tanah Loe Village, Garrangkeke Subdistrict, Bantaeng Regency through community service programs. Our efforts in this area of ​​community service are counseling through presentations and dissemination of materials to the community, question and answer sessions or discussion and evaluation. From the community service activities, it can be concluded that the knowledge and understanding of the people of Tanah Loe Village, Garrangkeke Subdistrict, Bantaeng Regency are increasing regarding clean and healthy lifestyle to avoid risk factors for typhoid fever infection. Keywords : Typhoid Fever, Tanah Loe Village, Clean and Healthy Lifestyle